Teoría y experiencias en el incremento de ductilidad de los hormigones de alta resistencia reforzados con fibras de acero - Fernández Cánovas, Manuel (Revista ALCONPAT, 2012)
Impact and impulsive loads such of those caused by missile and aircraft impact on nuclear containers or big liquated gas reservoirs, vehicles or ships in collision with bridges piles or offshore structures, or by blast waves on civil and military buildings or shelters, have played an important role in civil engineering, but today these actions reach a transcendental role because the proliferation of terrorist menaces. The behaviour of structures under these actions must be different of traditional ones, because of the big quantity of energy they must absorb and dissipate in a very short time, so structural elements formed by reinforced concrete must have ductility enough to reach large anelastic strains without failure. In tests carried out by us in highstrength concrete structural elements under impact of projectiles or dynamic actions, similar to those produce by seismic movements, we have checked how with a confinement by means of steel stirrups with the complement of steel fibers is possible to reach a notable ductility. The goal of this article is to present the results of some research works carried out showing the behaviour of reinforced concrete with steel fibers elements against these type of actions.Keywords: ductility; impact; impulsive loads; earthquake; high strength concrete; steel fibers; scabbing.